2021
DOI: 10.3390/jcm10132948
|View full text |Cite
|
Sign up to set email alerts
|

Steroid-Sparing Effect of Tocilizumab and Methotrexate in Patients with Polymyalgia Rheumatica: A Retrospective Cohort Study

Abstract: Polymyalgia rheumatica (PMR) is an inflammatory disorder characterized by pain and stiffness in the shoulders, hips, and proximal limbs; it usually affects elderly patients. The effectiveness of methotrexate and tocilizumab in PMR treatment has not been extensively studied. Thus, we aimed to assess the steroid-sparing effect of tocilizumab and methotrexate in PMR in clinical practice. Consecutive patients with PMR in our hospitals, who were included in our retrospective cohort, were reviewed between 2005 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 19 publications
0
22
0
2
Order By: Relevance
“…Three studies were excluded because we did not find data on the statistical significance or the studies did not pass the quality appraisal evaluation. Therefore, we included eight articles in this review [4,[11][12][13][14][15][16][17]. The PRISMA flowchart is illustrated in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three studies were excluded because we did not find data on the statistical significance or the studies did not pass the quality appraisal evaluation. Therefore, we included eight articles in this review [4,[11][12][13][14][15][16][17]. The PRISMA flowchart is illustrated in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…In PMR, Izumi et al reported no relapses in the TCZ group at the last follow-up visit in their investigation [14]. Bonelli et al's primary efficacy endpoint was to reach GC-free remission at week 16.…”
Section: Rate Of Flares and Remission Ratesmentioning
confidence: 98%
See 2 more Smart Citations
“…Controlling inflammation in CIRDs may provide additional clinical benefits, including prevention of chronic diabetes complications, reduction in cardiovascular morbidity and mortality, improvement of quality of life and medication adherence, as well as reduction in healthcare costs related to disease relapses and hospitalizations. The use of DMARDs in CIRD patients can also be advantageous in reducing the daily corticosteroid dose (steroid-sparing effect) [ 203 ], thereby mitigating the risk of incident diabetes (including steroid-induced diabetes, which is highly prevalent in these patients) [ 204 , 205 ] or preventing poor glucose control in diabetic subjects. Indeed, prolonged corticosteroid exposure deriving from long-term corticosteroid therapy leads to diabetogenic effects by enhancing hepatic endogenous glucose production and inducing insulin resistance in all insulin-sensitive tissues [ 206 ].…”
Section: Discussionmentioning
confidence: 99%